A single nucleotide polymorphism on the GALNT14 gene as an effective predictor of response to chemotherapy in advanced hepatocellular carcinoma. Issue 5 (3rd September 2013) - Yeh, Chau‐Ting; Liang, Kung‐Hao; Lin, Chen‐Chun; Chang, Ming‐Ling; Hsu, Cheng‐Lung; Hung, Chien‐Fu
Abstract : Previously, a pilot genome‐wide association study has identified candidate single nucleotide polymorphism predictors for the therapeutic response of 5‐fluorouracil, mitoxantrone and cisplatin (FMP) combination chemotherapy in advanced hepatocellular carcinoma (HCC). Here, we conducted a prospective confirmatory study to examine the predictive value of rs9679162 (located on GALNT14 gene) for the therapeutic responses using a split‐dose FMP protocol. One hundred and seven advanced HCC patients receiving split‐dose FMP therapy were enrolled. All patients were in Barcelona Clinical Liver Cancer Stage C with either main portal vein thrombosis and/or distant metastasis. Of them, 105 (98.1%) were Child‐Pugh classification B. GALNT14 genotype was determined before therapy. Of the patients included, 28 were rs9679162 "TT" and 79 were "non‐TT" ("GG" + "GT") genotype. The median overall survival, time‐to‐progression, response rate and disease control rate were ("TT" versus "non‐TT") 6.8 versus 3.9 months ( p < 0.001), 3.9 versus 2.1 months ( p < 0.001), 28.6% versus 10.1% ( p = 0.029) and 35.7% versus 15.2% ( p = 0.030), respectively. Multivariate analysis indicated that rs9679162 genotype was an independent predictor for overall survival ( p = 0.002). Categorical analysis showed that 17 patients with "TT" genotype, tumor size < 10 cm and neutrophils < 74% had a median overall survival of 25.5 months and a therapeutic response rate of 47.1%. In conclusion, this prospective study confirmed that GALN14 genotype (rs9679162) was an effective predictor for therapeutic outcome in advanced HCC patients treated by FMP chemotherapy. Combining GALNT14 genotype and clinical parameters, a subgroup of patients with excellent outcome was identified. Abstract : What's new? Thanks to the previous discovery of a single nucleotide polymorphism (SNP) in GALNT14, it may be possible to predict how patients with advanced hepatocellular carcinoma (HCC) will respond to therapy with 5‐fluorouracil, mitoxantrone, and cisplatin (FMP). Here, the predictive value of the SNP, known as rs9679162, is confirmed. In addition, a subgroup of patients with the "TT" GALNT14 genotype, whose tumors measured less than 10 cm and whose neutrophil levels in the blood were less than 74 percent, could achieve an excellent therapeutic response rate (47.1 percent) and long median overall survival (25.5 months).